Validating a segment on chromosome 7 of japonica for establishing low-cadmium accumulating indica rice variety - Kai Wang; Tian-ze Yan; Shi-long Xu; Xu Yan; Qun-feng Zhou; Xin-hui Zhao; Yan-feng Li; Zhong-xiu Wu; Peng Qin; Chen-jian Fu; Jun Fu; Yan-biao Zhou; et al. (Scientific Reports, 2021)
Abstract Cadmium (Cd) contamination of rice is a serious food safety issue that has recently been gaining significant public attention. Therefore, reduction of Cd accumulation in rice grains is an important objective of rice breeding. The use of favourable alleles of Cd accumulating genes using marker-assisted selection (MAS) is theoretically feasible. In this study, we validated a segment covering OsHMA3-OsNramp5-OsNramp1 on chromosome 7 of japonica for establishing low-cadmium accumulating indica rice variety. The OsHMA3-OsNramp5-OsNramp1 jap haplotype significantly decreased grain Cd concentration in middle-season indica genetic background. The improved 9311 carrying the OsHMA3-OsNramp5-OsNramp1 jap haplotype with recurrent parent genome recovery of up to 91.6% resulted in approximately 31.8% decrease in Cd accumulation in the grain and with no penalty on yield. There is a genetic linkage-drag between OsHMA3-OsNramp5-OsNramp1 jap and the gene conditioning heading to days (HTD) in the early-season indica genetic background. Because the OsHMA3-OsNramp5-OsNramp1-Ghd7 jap haplotype significantly increases grain Cd concentration and prolongs growth duration, the linkage-drag between OsHMA3-OsNramp5-OsNramp1 and Ghd7 should be broken down by large segregating populations or gene editing. A novel allele of OsHMA3 was identified from a wide-compatibility japonica cultivar, the expression differences of OsNramp1 and OsNramp5 in roots might contribute the Cd accumulating variation between japonica and indica variety.